2019
DOI: 10.2147/cpaa.s213271
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of the pharmacist in improving inhaler technique and asthma management in rural areas in Jordan</p>

Abstract: Introduction Pharmacists can have a valuable role in educating patients on correct inhaler technique leading to improved asthma management. Rural areas can benefit from the role of the pharmacist considering the barriers found in attending primary health-care facilities. Objectives This study aimed to assess the impact of inhaler technique education delivered by pharmacists on patients’ inhaler technique, Asthma Control Test (ACT) score, forced expiratory volume in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 43 publications
5
26
0
2
Order By: Relevance
“…Moreover, only 30% of the adult patients that took part in a recent Jordanian study were reported to have achieved asthma control [20]. A study from northern of Jordan showed that smoking is the main cause of poor asthma control in adolescent[4] and two studies from Jordan attributed poor control to non-adherence or improper use of inhalers [21, 22]; moreover one study showed a significant association between the level of asthma control and genetic in Arab population [23]. However, this issue is rarely investigated in the south of Jordan and the burden of uncontrolled asthma on patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only 30% of the adult patients that took part in a recent Jordanian study were reported to have achieved asthma control [20]. A study from northern of Jordan showed that smoking is the main cause of poor asthma control in adolescent[4] and two studies from Jordan attributed poor control to non-adherence or improper use of inhalers [21, 22]; moreover one study showed a significant association between the level of asthma control and genetic in Arab population [23]. However, this issue is rarely investigated in the south of Jordan and the burden of uncontrolled asthma on patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, 50% to 81% of patients do not use their inhalational devices accurately, in particular, older patients preparing the dose in the wrong orientation which are the common errors [ 20 - 21 ]; in our study, most of the participants were older patients who could not perform the crucial step 3, 5 and 6 correctly. Few observational studies are more concerned about many health professionals do not use inhalers accurately [ 22 - 23 ] and their role being evaluated by a few countries [ 24 ]. Therefore, health care providers are not in a position to assess and coach patients' inhaler technique effectively as noted in Table 2 ; pharmacy salesman is the main trainer (38%) who educates patients on inhaler technique but with major errors, while 16% reported that their prescribing doctors taught them the technique with less errors while performing their inhaler technique with optimal seven steps.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT is a validated patient-based tool that is usually used to evaluate asthma control in clinical practice. 22,28,29 It is recommended by the American Thoracic Society/ European Respiratory Society Task Force as an assessment tool of asthma control. 30 It is a questionnaire consisting of five questions; four of them are related to symptoms and use of relievers and one question is about patient self-assessed level of control.…”
Section: The Questionnairesmentioning
confidence: 99%
“…28,29,31 ACT reflects asthma patients' status during the last 4 weeks using a total score ranging from 5 to 25, with higher scores indicating a better asthma control. 22,29 Asthma patients who had scores between 20 and 25 were classified as well controlled; 16-19 as partially controlled; and 5-15 as poorly controlled. 31 In this study, a validated Arabic version of the ACT test was used.…”
Section: The Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation